KEPEMIMPINAN PERSPEKTIF ALQURAN; INTERPRETASI SEMIOTIK QS. AL-BAQARAH (2): 30-34 - Muttaqin, Enjen Zaenal (AT-TAISIR: Journal of Indonesian Tafsir Studies, 2020)
This paper discusses the issue of leadership in QS. Al-Baqarah (2): 30-34. The data in this paper will be analyzed through Charles Sanders Pierce's Semiotics approach. This article describes several factors that are often used as benchmarks for becoming a leader, namely spiritual piety, lineage and knowledge capacity. According to the Alquran, leadership is not about how pious or descended from blue blood or aristocracy, but rather who has the capacity (knowledge) to become a leader regardless of the origin of their descendants